Social Actions of Social Networks Users Triggered by Media Posts Content - Zakharchenko, Artem (Social Welfare: Interdisciplinary Approach, 2018)
Media posts spread throughout social networks due to their ability to call the readers to actions which is the sign of their influence. These actions can be considered both as social and communicative. Therefore, they can be studied in relation with other social actions taken by the same users offline: participation in mass protests, purchase of goods, downloading mobile applications, etc.The research has shown that not every share means the readiness for such offline actions. Most often this readiness is observed if media posts on a particular topic are shared through goal-rational actions and at the same time have a high influence on the audience. This influence is assessed by the author’s methodology of determining the interactive potential.The research has also found that while the news is spread among the politically active Ukrainians, the proportion of different types of shares varies depending on the indicator of publication influence on the audience. For publications with high influence indicator, goal-rational and value-based shares are the most typical and if the indicator is low, the affective spreading occurs.
Keywords: social action; social networks; interactive potential; media audience; information spreading